1998
DOI: 10.1074/jbc.273.3.1832
|View full text |Cite
|
Sign up to set email alerts
|

p38 Kinase Activity Is Essential for Osmotic Induction of mRNAs for HSP70 and Transporter for Organic Solute Betaine in Madin-Darby Canine Kidney Cells

Abstract: In renal cells, hypertonicity induces genes for heat shock proteins (HSP70, ␣B-crystallin), as well as enzymes and transporters directly involved in the metabolism and transport of protective organic osmolytes. While heat shock proteins are induced by many stresses including osmotic stress, the induction of the osmolytes genes appears to be specific to osmotic stress. These two adaptive mechanisms allow kidney cells to survive and function in the hypertonic environment that exists on routine basis in kidney me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
148
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 45 publications
(69 reference statements)
14
148
1
Order By: Relevance
“…A p38-dependent pathway was recently implicated in the hypertonic induction of betaine and myoinositol transport in human monocytes (43) and of betaine transport in Madin-Darby canine kidney cells (44). However, although cell volume changes were not monitored in either of those reports, cell transfer to hypertonic medium is expected to cause an abrupt shrinkage rather than a gradual and progressive decrease of cell volume, as observed here.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A p38-dependent pathway was recently implicated in the hypertonic induction of betaine and myoinositol transport in human monocytes (43) and of betaine transport in Madin-Darby canine kidney cells (44). However, although cell volume changes were not monitored in either of those reports, cell transfer to hypertonic medium is expected to cause an abrupt shrinkage rather than a gradual and progressive decrease of cell volume, as observed here.…”
Section: Discussionmentioning
confidence: 47%
“…The p38 inhibitor SB203580 (1 M), added to the extracellular medium 60 min before amino acid-free incubation and maintained thereafter, produced a 60% inhibition of adaptive increase in system A transport activity. 2 However, the interpretation of this result is made difficult by the marked activation of JNK1 promoted by the inhibitor in our cells 2 as in other models (44). ERK1/2 kinases are markedly activated when cultured human fibroblasts (this report) or other cells (20 -22) are incubated under hypertonic conditions.…”
Section: Discussionmentioning
confidence: 64%
“…High glucose stimulation of cultured proximal tubular epithelial cells results in p38-dependent angiotensinogen production and p38-independent hypertrophy [37,38]. In addition, high glucose levels can increase the hypertonicity of the tubular fluid, resulting in greater osmotic stress to tubules, which is known to induce p38 phosphorylation in cultured tubular cells [39]. In the current study, dilated tubules in diabetic kidneys appeared to have an increased proportion of p-p38+ cells, suggesting that increased phosphorylation of tubular p38 also occurs in response to tubular injury.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting accumulation of glycerol in yeast cells maintains cellular turgor even after exposure to severe hyperosmotic stress. Elements of the HOG pathway have also been found in mammals, Drosophila , and plants (Han et al, 1994(Han et al, , 1998Popping et al, 1996) and shown either to be required for hyperosmotic adaptation (Sheikh Hamad et al, 1998) or to be capable of complementing corresponding yeast mutants (Kumar et al, 1995; Han et al, 1998).…”
mentioning
confidence: 99%